2004
DOI: 10.1086/422244
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement of the Electromagnetic Luminosity of a Kerr Black Hole

Abstract: Some active galactic nuclei, microquasars, and gamma ray bursts may be powered by the electromagnetic braking of a rapidly rotating black hole. We investigate this possibility via axisymmetric numerical simulations of a black hole surrounded by a magnetized plasma. The plasma is described by the equations of general relativistic magnetohydrodynamics, and the effects of radiation are neglected. The evolution is followed for $2000 G M/c^3$, and the computational domain extends from inside the event horizon to ty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
791
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 574 publications
(866 citation statements)
references
References 48 publications
(57 reference statements)
71
791
2
2
Order By: Relevance
“…Assuming that the jet power increases with BH spin as P j ∼ a 2 * (McKinney & Gammie 2004;Blandford & Znajek 1977), the discrepancy between halo and core jet power cannot be removed even if an extremely fast-rotating BH (a * = 0.998) is assumed. The most likely explanation is probably that the accretion rate is much lower now than it was a few million years ago.…”
Section: The Jet Powermentioning
confidence: 99%
“…Assuming that the jet power increases with BH spin as P j ∼ a 2 * (McKinney & Gammie 2004;Blandford & Znajek 1977), the discrepancy between halo and core jet power cannot be removed even if an extremely fast-rotating BH (a * = 0.998) is assumed. The most likely explanation is probably that the accretion rate is much lower now than it was a few million years ago.…”
Section: The Jet Powermentioning
confidence: 99%
“…The most successful models are those that involve the extraction of rotational energy from the accretion disk (Blandford & Payne 1982) or of the black hole itself (Blandford & Znajek 1977) through the magnetic field. Some numerical simulations (McKinney & Gammie 2004;De Villiers et al 2005) have suggested that launching from the accretion disk can only produce jets with moderate Lorentz factors (Γ < 3), while a process involving the black hole rotation can achieve Γ ∼ 10 more easily (McKinney 2006). However, it is not ruled out that the inner disk can launch relativistic jets as well (Vlahakis & Königl 2004;Komissarov et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, numerical implementations for GRMHD simulation in the fixed gravitational field have been extensively developed (e.g., [18,17,[19][20][21][22][23][24]). In particular, it is worth to mention that Refs.…”
Section: Introductionmentioning
confidence: 99%